Making terrains: Surveying, drones and media ecology. Issue 2 (4th May 2019) - Milligan, Brett
Abstract: Site surveys are foundational to the design of landscapes. Rapid technological innovations have caused the range of phenomena that can be surveyed and the forms that landscape surveys can assume to radically expand. This article presents findings from two long-term site surveying experiments using drones, real-time kinematic surveying equipment, photogrammetry, GIS and 3D modelling software. Rather than focusing on drones as objects, attention is placed on the aesthetic and techno-experiential interpretation of sites through a media ecology approach, examining the co-constructive, qualitative relationships among technology, humans and landscapes. Research results describe the unique capacities drone technologies can provide, emphasizing the modelling of site-specific, spatiotemporal landscape change over time, and expanded techno-aesthetic capacities for fieldwork and sensing of place. These results are compared with other modes of site modelling to discuss differences. Conclusions posit that a media ecology approach can provide effective tools to critically assess modes of landscape interpretation at a time when technical means to encounter landscapes continue to diversify.